EVALUASI PROGRAM PENCEGAHAN DAN PENGENDALIAN DEMAM BERDARAH DENGUE PADA MASA PANDEMI COVID-19 (Studi Kasus di Puskesmas Temanggung) - Farah Veda Norisa; Dyah Mahendrasari Sukendra (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2022)
In the beginning of 2020, dengue fever cases rose in Indonesia. From January 1 to March 11, 2020, there were 17.820 cases recorded and 104 of which had died. The dengue fever cases always rise every year even to be an endemic disease almost in all Indonesia’s provinces. In 2019, Puskesmas Temanggung had IR Dengue Fever valued at 171.62/100.000 habitants which means still far away from either national target (<51/100.000 habitants) or strategic plan target (<46/100.000 habitants). Its precaution and control programs held by Puskesmas Temanggung, those are “Batik Tulis”, “Grebeg Jentik”, routine counseling and epidemiologic research. Applied indicator to assess the dengue fever attempt is flick-free rate. The type of this research is quantitative research by case-study approach. Data collection technique implemented by semi-structured interview and documentation study, with the main informants are the head of Puskesmas Temanggung, epidemiologic surveillance of Puskesmas Temanggung, P2P Dengue Fever director of Puskesmas Temanggung, and environment hygienic sanitary of Puskesmas Temanggung while triangulation informants are tocologist in working area of Puskesmas Temanggung. Utilized research instruments are interview guide and voice recorder. The interview guide was divided into two, the first guide addressed to the main informant and the second guide addressed to triangulation informant. Applied data analysis techniques are data reduction, data display and conclusion drawing/verification while descriptive patterns are used in data display.